Medroxyprogesterone acetate improves propionic acid-induced autism rat model and magnetic resonance spectroscopic correlation (Bangladesh Journal of Pharmacology, 2022)
The protective effect of medroxyprogesterone acetate on propionic acid-induced autism in rats was evaluated. For this purpose, 30 rats were divided into three groups. The significant difference in the levels of IL-17 (p